Liquid-liquid Extraction of Lactic Acid from Aqueous Medium Using Menthol-lauric Acid and Thymol-lauric Acid Deep Eutectic Solvent - OBISIKE, Mercy Ijeoma; AMEH, Alewo Opuada; BELLO , Tajudeen Kolawole (ABUAD Journal of Engineering and Applied Sciences, 2023)
Chemistry is paying more attention to deep eutectic solvents, a kind of environmentally benign solvent that may be used to extract and separate target molecules from a variety of samples. This paper focuses on the use of non-ionic hydrophobic-based deep eutectic solvents (DES) for the extraction of lactic acid from an aqueous medium and to determine the physiochemical properties that make them unique from other extraction solvents. According to the results of this work, a ternary phase diagram composed of menthol and lauric acid (1:1) and thymol and lauric acid (1:1) was determined at 298.15 K and atmospheric pressure. The tie lines show that the raffinate phase contains no DES and the extract phase contains no water in it. This is an important advantage of DES as a solvent compared to organic solvents since it could reduce the number of purification steps in the extraction unit and thus reduce its operating cost. The synthesised DESs’ component FTIR spectra were examined. The findings revealed shifts (stretch and vibration) that may be related to interactions, structural modifications, and the development of chemical bonds between the bands at 3242 (cm⁻¹) and 3417 (cm⁻¹). The density values of DES A range from 0.897 to 0.853 g/cm3, and those of DES B fall between 0.936 and 0.837 g/cm3. The synthesised DESs’ surface tensions were tested; DES A displayed a greater surface tension of 31.14 mN/m, while DES B displayed a lower surface tension of 29.29 mN/m. These surface tension values fall within the literature range of 20–60 mN/m for DESs; hence, they can be used as a potential alternative solvent to conventional organic solvents for lactic acid extraction owing to their attractive and eco-friendly properties. The systems displayed a higher extraction efficiency of 99%, indicating the potential use of DESs as solvents for the separation of lactic acids from an aqueous medium.